Potensi Kandungan Antioksidan dari Daun Rhizophora apiculata Mangrove Khas Lempasing, Pesisir Lampung Selatan - Muhammad Yogi Saputra; Muhammad Raffi Zakaria; Debora Silalahi; Welldone Sartika; Hamdiyah Fuola Zeri Hasibuan; Rahmat Kurniawan; Arif Azhari; Sena Maulana; Syaikhul Aziz; Sukrasno Sukrasno (Stannum : Jurnal Sains dan Terapan Kimia, 2022)
The mangrove woodland is a distinct bush or brine habitat characterized by a coastal sedimentation environment in which fine sediment (often rich in organic matter) accumulates in areas protected from high energy waves. Mangrove forests thrive on the coasts of tropical and subtropical regions, including Indonesia. Mangrove forest is a complex ecosystem that has a high diversity of plants, microorganisms, and animals. One of them is the Oil Mangrove (R. apiculata) which grows well on the coast of Lampung. This plant is hard, rich in tannins, and dense, mainly used to make charcoal and firewood. This plant traditionally used to treat diarrhea and nausea. Mangrove plants are tolerant to high salt levels, this special trait is due to the presence of secondary metabolites produced in response to various environmental stresses. Flavonoid compounds, alkaloids, terpenoids and steroids are secondary metabolites produced by mangrove plants. Secondary metabolite compounds from mangroves have bioactivity such as antidiabetic, antimicrobial, antioxidant and anticancer. Exploration of secondary metabolites from mangroves, especially oil mangroves locally named as Bakau Minyak, which are widely grown in the Lempasing area, coastal Lampung for the development of medicinal compounds, has not been intensely reported. This investigation aims to study the potential phytochemicals profile of R. apiculata’s leaf as an antioxidant